An evaluation of local policies and actions that address climate change in Turkish metropolitan cities. Issue 3 (4th March 2018) - Gedikli, Bahar; Balaban, Osman
ABSTRACT: As sites of climatic impacts, cities have become key players in climate policy-making in order to reduce GHG emissions and vulnerabilities of settlements. They started taking actions in various fields such as built environment, water and waste management, transportation and urban greenery. However, the involvement of cities in climate policy-making varies over countries and regions; the extent of involvement differentiates even among the cities of the same country. This paper focuses on the Turkish case and elaborates the current status of climate policy-making in Turkish metropolitan cities. It aims at identifying achievements at the local level and pointing to challenges for an effective local climate action, which can be helpful for other contexts, too. Having conducted both desk-based and questionnaire surveys, it examines and categorizes climate-related actions in metropolitan municipalities, and highlights varying levels of achievements in terms of sectors and innovativeness. The study concludes with analysing the motives behind varying achievements of municipalities as well as the main challenges for local action and discussing policy implications to overcome them.